Pengaruh Harga Tiket terhadap Loyalitas Penumpang pada Maskapai Lion Air di Bandar Udara Mopah Merauke - Ekawati, Dyah Ayu; Astutik, Septiyani Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Mopah Airport Merauke is one of the airports located in the city of Merauke, South Papua, Indonesia. The purpose of this study is to find out whether ticket prices affect passenger loyalty, and how much ticket prices affect passenger loyalty at Mopah Airport Merauke. This research uses quantitative methods. The research was conducted at Mopah Airport Merauke where the passengers or people in the city of Merauke were the objects of this research. The source of the data used in this study was obtained from the results of distributing questionnaires to passenger respondents at Mopah Airport Merauke. The number of samples in this study were 100 respondents determined by the slovin formula. The results of the study were concluded to answer the formulation of the problem, that: 1. The ticket price variable (X) has an effect on passenger loyalty (Y) as evidenced by the calculated T value on the ticket price influence variable (X) which is greater than T table, namely 3,580 > 1,660 with a Sig value . smaller than the probability value, namely 0.01 <0.05; 2. Ticket prices (X) have an effect on Passenger Loyalty (Y) of 0.116, it is known from the R Square value, which means that the X variable affects the Y variable by 11.6%.. Keywords : ticket prices, loyalty, passengers, mopah airport merauke.